Production of Cycloalkanes in Hydrodeoxygenation of Isoeugenol Over Pt- and Ir-Modified Bifunctional Catalysts - Louis Bomont; Moldir Alda‐Onggar; Vyacheslav Fedorov; Atte Aho; Janne Peltonen; Kari Eränen; Markus Peurla; Narendra Kumar; Johan Wärnå; Vincenzo Russo; Päivi Mäki‐Arvela; Henrik Grénman; et al. (My University, 2022)
Hydrodeoxygenation of isoeugenol was investigated at 200 °C under 3 MPa total pressure in dodecane as a solvent, in hydrogen, over bifunctional Pt‐ and Ir‐modified Beta zeolites and mesoporous materials. As a comparison, Pt and Ir supported on Al2O3, SiO2 and mesoporous MCM‐41 were also tested. The catalysts were characterized by XRD, CO pulse chemisorption, transmission electron microscopy, scanning electron microscopy, nitrogen adsorption and FTIR pyridine adsorption desorption. The results revealed that the most active and selective catalyst was Pt‐H‐Beta‐300, which exhibits the lowest acidity and largest crystal size of Beta zeolite among the studied Pt‐ and Ir‐modified Beta zeolites. Complete conversion of isoeugenol and 89 % selectivity to propylcyclohexane was obtained with this catalyst in 240 min. The overall deoxygenation selectivity was 100 %, giving dialkylated cyclohexanes as the second major product. The catalyst was regenerated, reduced and reused in the hydrodeoxygenation of isoeugenol with almost the same performance as the fresh catalyst. Thermodynamic analyses and kinetic modelling of the data were also performed.